(untitled) (Bangladesh Journal of Child Health, 2020)
Cornelia de Lange syndrome (CdLS) is a rare syndrome of multisystem disorder. Almost every system is involved in this disorder having growth retardation, facial dysmorphism, short stature, psychomotor delay and behavioral problems. Diagnosis is made on the basis of clinical observations, physical examination, laboratory tests and X-rays; chromosome analysis is usually conducted before a diagnosis is made. DNA testing is helpful for confirmation of the clinical diagnosis. A 10 year old boy presented with short stature, facial dysmorphism, microcephaly, mental retardation and micromelia. DNA analysis revealed heterozygous mutation in NIBPL gene. Patient was counseled about the diagnosis and treatment was given. We reported the case due to rarity of the disease. Bangladesh J Child Health 2020; VOL 44 (1) :52-54